The impact of climatic variability over the period 1961- 1990 on the soil water balance of upland soils in the North East Arid Zone of Nigeria - Hess, Tim M. (Cranfield University, 1991)
Over the period 1961 – 90 the North East Arid Zone of Nigeria experienced a decline in annual rainfall totals and increased aridity which placed increasing pressure on rain fed, millet-based farming systems. The changes in seasonal rainfall total and distribution have been examined and it has been shown that the rate of decline has been consistent across the region. The decline has been dominated by reduction in the number of rain days during the middle of the rainy season and there is no evidence of a significant change in the length of the growing season. Over the same time period, there has been a small, but significant, increase in mean air temperature which has resulted in a small increase in potential evapotranspiration. Other climatic parameters (vapour pressure, solar radiation and wind speed) appear to have remained stable, although the paucity and dubious quality of much of the historical meteorological data make rigorous statistical analysis difficult. A water balance model (BALANCE) developed by the author, was calibrated for a millet crop grown on a typical sandy loam soil in Maiduguri (Nigeria). The model was necessarily parsimonious, but was shown to perform well when calibrated against observed soil water content. However, the empirical nature and high sensitivity of key parameters relating to bare soil evaporation and drainage mean that it is difficult to parameterise the model by laboratory, or independent field measurements. Applying the calibrated model to daily rainfall and average evapotranspiration data from Nguru (Nigeria) for the period 1961 – 93 showed that, with the exception of extreme drought years, the increased aridity would have had little impact on the viability of traditional millet and millet-cowpea intercropping systems prior to the early 1980s. However, after that date, predicted seasonal millet transpiration, and hence predicted yields, have declined, and long duration cowpea intercrops, which were traditionally matured on residual soil moisture after the millet harvest have had insufficient water. Whilst the BALANCE model has been useful in examining the impact of climatic variability on agro-hydrology, it is not a crop physiological model and the interaction between soil water and crop development is poorly represented. The model cannot, therefore be applied with confidence to investigate the potential yield benefits of physical or agronomic interventions to alleviate the impacts of aridity. Although more complex models exist to do this, they require detailed parameterisation of the crop physiology, which was not possible within the scope of this study.